2023
DOI: 10.1111/cas.15802
|View full text |Cite
|
Sign up to set email alerts
|

Association of mesothelioma deaths with neighborhood asbestos exposure due to a large‐scale asbestos‐cement plant

Abstract: A causal relationship between mesothelioma and occupational asbestos exposure is well known, while some studies have shown a relationship to non-occupational exposures. The aim of this study was to quantify the risk of mesothelioma death associated with neighborhood asbestos exposure due to a large-scale asbestos-cement (AC) plant in Amagasaki, Japan, adjusting properly risk factors including occupational exposures.We conducted a nested case-control study in which a fixed population of 143,929 residents who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…In addition, the availability of longitudinal exposure patterns based on patient residential history may have important implications, such as tracking the inducement and survival conditions for mesothelioma patients, investigating susceptible time window and latency period, studying disease development of mesothelioma and different cancer types. While the current study was a case-only design and specific to mesothelioma which has a known etiology, our methods can be applied to future studies with comparison groups to further study mesothelioma patients, as have been shown in other studies based on population-level mesothelioma registries where residential history information is available, as well as other cancer types ( 7 - 9 , 11 , 12 , 31 - 33 ). With increasingly available geocoding and geospatial analytical tools, as well as refined data on environmental and socioeconomic factors, utilization of patients’ residential history as opposed to single address at diagnosis will lead to improved exposure and health risk estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the availability of longitudinal exposure patterns based on patient residential history may have important implications, such as tracking the inducement and survival conditions for mesothelioma patients, investigating susceptible time window and latency period, studying disease development of mesothelioma and different cancer types. While the current study was a case-only design and specific to mesothelioma which has a known etiology, our methods can be applied to future studies with comparison groups to further study mesothelioma patients, as have been shown in other studies based on population-level mesothelioma registries where residential history information is available, as well as other cancer types ( 7 - 9 , 11 , 12 , 31 - 33 ). With increasingly available geocoding and geospatial analytical tools, as well as refined data on environmental and socioeconomic factors, utilization of patients’ residential history as opposed to single address at diagnosis will lead to improved exposure and health risk estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of diagnosis is 72 years for the malignant pleural mesothelioma, the major form of mesothelioma, and the 5-year relative survival rate is only 12% ( 4 ). Workplace asbestos exposure is the dominant contributor to mesothelioma, though para-occupational (or take-home) exposure and environmental exposure to asbestos (e.g., residing in close proximity to asbestos sources) also play a critical role of mesothelioma development ( 5 - 9 ). Studies from mesothelioma registries in many countries have been instrumental in providing rich information, including specifically residential histories, to understand the impact of asbestos exposure at scale, and to investigate known and unknown asbestos exposure sources ( 8 , 10 - 12 ).…”
Section: Introductionmentioning
confidence: 99%